The Efficiency of the Japanese Equity Market - Nagayasu, Jun (IMF Working Papers; Working Paper ;, 2003)
Using the ARFIMA-FIGARCH model, this paper studies the efficiency of the Japanese equity market by examining the statistical properties of the return and volatility of the Nikkei 225. It shows that both follow a long range dependence, which stands against the efficient market hypothesis (EMH). The result is valid for all sample periods, suggesting that the recent equity market reform has not produced major efficiency gains.